MECHANISM OF MODIFIED PEONY DECOCTION IN ALLEVIATING CONCURRENT LUNG AND INTESTINAL BARRIER INJURY IN ULCERATIVE COLITIS RATS VIA RHO/ROCK/NF-?B PATHWAY - Xinyu Zhan; Huiyan Xu; Haimei Zhang; Yongsen Jia; Fanwu Wu; Lingyu Kong; Xin Yan (Journal of Animal and Plant Sciences, 2026)
<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Ulcerative colitis (UC) is characterized by its tendency to relapse and difficulty in cure. The Rho/ROCK/NF-κB pathway serves as a critical regulatory axis in UC. However, the mechanism by which traditional Chinese herbal compounds modulate this pathway to ameliorate concurrent lung and intestinal barrier injury remains incompletely elucidated. <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: SimSun; mso-fareast-theme-font: minor-fareast; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">The aim of this study was <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">to investigate therapeutic mechanism of <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: SimSun; mso-fareast-theme-font: minor-fareast; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">m<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">odified peony<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: SimSun; mso-fareast-theme-font: minor-fareast; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;"> d<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">ecoction in alleviating lung–gut barrier damage in UC rats via Rho/ROCK/NF-κB pathway, thereby addressing the current gap in both therapeutic strategies and mechanistic research in this field. <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: SimSun; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Thirty specific-pathogen-free adult male Wistar rats were subcutaneously injected with 8 mg of antigen emulsion in the groin area, followed by slow intra-colonic administration of a 2,4,6-trinitrobenzenesulfonic acid (TNBS)/50% ethanol mixture at 5 cm from the anus to establish the UC model. Successfully modeled rats were randomly divided into five groups (n=6 per group): the UC group (administered 10 mL/kg saline by gavage), the mesalazine group (MESA group, administered 0.5 g/kg mesalazine by gavage), the low-dose group (LD group, administered 6 g/kg modified peony decoction by gavage), the medium-dose group (MD group, administered 12 g/kg modified peony decoction by gavage), and the high-dose group (HD group, administered 24 g/kg modified peony decoction by gavage). All groups received daily gavage for 28 consecutive days. Additionally, six non-modeled rats served as the blank control group (BC group) and were administered 10 mL/kg saline by gavage. <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">The distinctions in body weight (BW) and disease activity index (DAI) were analyzed after gavage treatment. Rat lung and colon tissues were collected for histopathological changes observed by HE staining, and F-actin (F-act), VE-cadherin (VE-cad), and ZO-1 was observed by immunofluorescence staining. Rho/ROCK/NF-κB pathway and key proteins of the mucosal barrier were detected by Western blot<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: SimSun; mso-fareast-theme-font: minor-fareast; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">ting<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">. As against BC group, UC group <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: SimSun; mso-fareast-theme-font: minor-fareast; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">d<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">emonstrated weight loss and increased DAI scores; lung and colon tissues exhibited disordered structure and inflammatory cell infiltration; the decreased expression intensity of F-act, VE-cad, and ZO-1, and increased p-Rho A, ROCK1, NF-κB, COX-2, and VEGF. As against UC group, MESA, LD, MD and HD group<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: SimSun; mso-fareast-theme-font: minor-fareast; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">s<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;"> <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: SimSun; mso-fareast-theme-font: minor-fareast; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">e<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">xhibited increased BW and decreased DAI scores; the significant improved pathological damage of lung and colon tissues; the increased expression intensity of F-act, VE-cad, and ZO-1, and the decreased p-Rho A, ROCK1, NF-κB, COX-2, and VEGF. The HD group <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: SimSun; mso-fareast-theme-font: minor-fareast; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">e<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">xhibited significant better improvement in all indicators than LD group and MD group (all P<0.05).<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: SimSun; mso-fareast-theme-font: minor-fareast; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;"> <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: SimSun; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">UC rats exhibited significant concurrent injury to both the lung and intestinal barriers. Treatment with different doses of modified peony decoction resulted in increased body weight, reduced DAI scores, markedly improved histopathological damage in lung and colon tissues, enhanced expression intensities of F-actin, VE-cadherin, and ZO-1, along with decreased expression levels of p-RhoA, ROCK1, NF-κB, COX-2, and VEGF. The high-dose group demonstrated significantly greater improvement in all these indicators compared to the low- and medium-dose groups, showing that modified peony decoction alleviates lung-intestinal barrier injury in UC rats via the Rho/ROCK/NF-κB pathway.<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">
Keywords: modified peony decoction; ulcerative colitis; concurrent lung and intestinal barrier injury; tight junction